Analisis Pemahaman Nasabah terhadap Akad Jual Beli pada Perbankan Syariah - Grace Merienth Arha Silalahi; Irma Siagian; Twenty Desyen Manurung (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
This study aims to analyze the level of customer understanding of the sale and purchase agreement in Islamic banking and identify factors influencing this understanding through a literature review. The study used a qualitative method with descriptive analysis based on library research. The research data came from various secondary sources, including books, scientific journal articles, Islamic banking regulations, DSN-MUI fatwas, and official reports (OJK). The data analysis technique was conducted using content analysis based on the Miles, Huberman, and Saldaña model through the stages of data reduction and presentation, as well as drawing conclusions and verification. The results show that education level, length of customer experience, and intensity of socialization from Islamic banks are the main factors influencing customer understanding of the sale and purchase agreement. Customers with higher levels of education tend to have better abilities in understanding the concept of the agreement and distinguishing between profit margin and interest mechanisms. In addition, longer transaction experience contributes to increased understanding through an experiential learning process. Socialization conducted by banks has also been proven to play a significant role in improving public Islamic financial literacy. A good understanding of the sale and purchase agreement has a positive impact on product usage decisions, customer satisfaction, and loyalty to Islamic banking. This research emphasizes the importance of strengthening public education strategies, ensuring contract transparency, and improving Islamic financial literacy as efforts to support the sustainable development of the Islamic banking industry.